KREATIVITAS PESERTA DIDIK DALAM PEMANFAATAN BARANG BEKAS SEBAGAI MEDIA PEMBELAJARAN ILMU PENGETAHUAN ALAM (IPA) DI SD INPRES WATUBOSE - Faradilah, Faradilah; Rusdin; Irawan Hadi Patanggu (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research was motivated by the creativity of students in using used goods as a medium for learning Natural Sciences (Science) at SD Inpres Watubose. This research starts from the problem of how students are creative in using used goods in science learning and what types of creativity are produced through the use of used goods as a science learning medium at SD Inpres Watubose. This research uses a qualitative approach. Data collection techniques through observation, interviews and documentation. The data analysis technique used is by analyzing data in the form of qualitative data and then interpreting it using an inductive mindset, namely a way of thinking that starts from specific facts, concrete events from research, then drawing generalizations through general characteristics. And the presentation of the data used is to present the data that has been collected in a simpler form. From the results of this research it was found that: 1) implementing activities to utilize used goods as a learning medium at SD Inpres Watubose can foster creativity in students and students can manage used goods so that they can be reused 2) In activities utilizing used goods carried out in schools there are Several types of learning media are produced through students' creativity, including: human breathing apparatus, hand joint movement props and sound sources. All learning media are made by reusing used goods.